Artificial hand gripper controller via Smart Glove for rehabilitation process - Ashikin M., Mohd Ali; Radzi, Ambar; Muhammad Mahadi, Abdul Jamil, Dr.; Ahmad Jalaludin, Abdul Wahi; Siti Hajar, Salim (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/